Tuning circularly polarized luminescence of an AIE-active pyrene luminogen from fluidic solution to solid thin film. Issue 11 (16th March 2016) - Li, Junfeng; Yang, Chenglong; Huang, Chao; Wan, Yi; Lai, Wen-Yong
Graphical abstract: Circularly polarized luminescence from pyrene luminogen was modulated via fine-tuning the excited conformation from fluidic solution to solid thin films. Abstract: The photoluminescence (PL) and circularly polarized luminescence (CPL) of (( R )-1-phenyl- N -(pyren-1-ylmethyl)ethanamine)P -R were successfully modulated via fine-tuning and precise control of excited conformation of dimer/excimer by external stimuli. The resulting aggregation-induced emission (AIE)-active material (P -R ) exhibited CPL with a low dissymmetry factor (∼10 −4 ) in monomeric form, while demonstrating a prominent CPL signal with a higher dissymmetry factor (∼10 −3 ) in thin solid films even without annealing processes.